Advances in wearable impact sensors for monitoring and reducing brain injury risks due to cumulative head impact trauma in athletic and military environments. Issue 11 (25th May 2017) - Ralston, John; Thibado, Jason; Woodard, Jonathan
Abstract : Objective: Assess utility of wearable impact sensors to monitor and reduce cumulative brain injury risks in athletic and military environments. Design: Analysis of results generated in multiple laboratory and on-field cohort studies. Setting: Youth, college, and professional football, rugby, soccer, lacrosse, boxing; military training exercises. Participants: Participants across multiple activities were monitored for head impacts using wearable sensors. Intervention: Participants suffering a concussion underwent neurocognitive testing and entered a supervised return-to-play protocol. Outcome measures: The influence of sensor design and data processing on the accuracy and reproducibility of head impact data have been assessed. Differences in head impact incidence and severity have been compared between training regimes that did/did not implement behavioural modifications based on sensor data. Head impact data have been combined with finite element modelling and high resolution MRI/DSI imaging to study spatial distribution of tissue damage and changes in neural connectivity. Main results: Reduced size and weight skin-affixed sensors worn on the mastoid provide a stable and universally applicable solution for head impact monitoring. Behavioural modifications using these devices have reduced high risk head impacts by 30%−70%. Significant localised tissue damage and changes in neural connectivity are predicted and observed even in the absence of clinically diagnosed concussion symptoms. Conclusions: Wearable impact sensors are enabling significant reductions in head injury risks and incidence in athletic and military environments. These devices show promise as neuro-trauma dosimeters that can assist in monitoring cumulative brain damage due to repetitive sub-concussive head impacts, and developing more comprehensive and personalised remove-from-play thresholds. Competing interests: X2 Biosystems designs and manufactures wearable impact sensors